FAKTOR YANG MEMPENGARUHI E-BANKING READINESS PENGGUNA E-BANKING DI JAKARTA - Anthony, Hendro Lukman (Jurnal Paradigma Akuntansi, 2020)
This research aims to obtain empirical evidence about factorsthat affecting interest in using E-banking services in Jakarta. This research uses primary data obtained using questionnaire distributed to E-banking users in Jakarta. The population of this research is E- banking  users  in  Jakarta.  This  research  is  conducted  with  a  sample  of  110  data. Furthermore,  data  collection  techniques  used  in  this  research  is  primary  data  that  is processed using Statistical Package for the Social Sciences (SPSS) ver 21.0 software. The statistical method used to test the hypothesis is the multiple linear regression method. The results of this research show that factors such as usefulness, ease of use, convenience, and security and privacy has significant effect on interest in using E-banking services.